APOBEC3B: Future direction of liver cancer research - Yang, Xingyue; Dai, Jing; Yao, Shun; An, Jiaxing; Wen, Guorong; Jin, Hai; Zhang, Li; Zheng, Liming; Chen, Xingyue; Yi, Zhiqiang; Tuo, Biguang (Frontiers in Oncology, 2022)
Liver cancer is one of the most common cancers in the world. Its fatality rate is still at the top for the high invisibility of its illness, The main risk factor for liver cancer remains infection with the hepatitis B virus (HBV). Moreover, a considerable number of genetic and epigenetic factors are also directly or indirectly involved in the underlying pathogenesis of liver cancer. In particular, the apolipoprotein B mRNA editing enzyme catalytic peptide-like protein (APOBEC) family (DNA or mRNA editor family), who has been the focus of virology research for more than a decade. Recently, it has also been found that it plays a significant role in the occurrence and development of various different cancers, which provides us with a new direction of thinking for the research of liver cancer. APOBEC3B is a cytosine deaminase that controls a variety of biological processes such as protein expression, innate immunity, and embryonic development by participating in the process of cytidine deamination to uridine in DNA and RNA. In human, APOBEC3B has long been known as a DNA editor for limiting viral replication and transcription. As the matter of fact, APOBEC3B is widely low-expressed in a variety of normal tissues and organs, but significantly upregulated in different types of tumor tissues and tumor lines. This also makes APOBEC3B receive increasing attention in various cancers, but the role of APOBEC3B in the highly risk factors of liver cancer - infection with hepatitis B virus and the occurrence and development of liver cancer is still remains blurred. This review will provide a brief introduction to the pathogenesis of hepatocellular carcinoma caused by the development of hepatitis B virus. As well as further exploring the latest results of APOBEC3B research in the development of hepatitis B virus and liver cancer, it provides new directions and strategies for the treatment and prevention of liver cancer.